Effect of Changes in Land Use in Flood Disasters in Baleendah District, Bandung Regency - Barus, Lita; Tambunan, Rudy; Arif, Victorina (UI Scholars Hub, 2019)
Population growth and urbanization in Bandung Regency causes the need to increase. This encourages land conversion in open areas to become a built area to meet the needs of the community. Changes in land use avoid ecological imbalances between catchment areas and built areas. The flood phenomenon occurs in several districts in Bandung Regency every year, one of which is Baleendah District. The purpose of this study is to discuss changes in land use that occur in Baleendah District and discuss it with a flood disaster index. This study uses qualitative analysis of the exploration of secondary data and literature studies. Secondary data consisted of satellite image superimposition in 2003, 2006, 2009, 2013 and 2015. Then, the flood index used quantitative to increase the impact of the flood index that occurred in 2003, 2006, 2009, 2013 and 2015. Based on the results of the study, identified the existence of changes in flow in the river flow which increases the increase in the flood index.